2021
DOI: 10.1002/cpe.6232
|View full text |Cite
|
Sign up to set email alerts
|

Extending collaborative filtering recommendation using word embedding: A hybrid approach

Abstract: Summary Collaborative filtering recommendation systems, which analyze sets of user ratings, have been applied to various domains and have resulted in considerable improvements in the traditional recommendation system. However, they still have problems with data sparsity and cold‐start of the user ratings. To solve these problems, we present a hybrid recommendation approach by combining collaborative filtering methods and word embedding‐based content analysis. This study focuses on the movie domain, and therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 21 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…Recently, some studies [36][37][38] also proposed sophisticated collaborative filtering to improve recommendation performances. The study conducted by [36] suggested new collaborative filtering using cognitive similarity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some studies [36][37][38] also proposed sophisticated collaborative filtering to improve recommendation performances. The study conducted by [36] suggested new collaborative filtering using cognitive similarity.…”
Section: Discussionmentioning
confidence: 99%
“…We still need further study to compare both algorithms for higher k (i.e., k = 60 up to k = 100) because the cognitive similarity did not measure them. In addition, Nguyen et al [37] use word embedding to improve their proposed collaborative filtering. Hence, implementing word embedding in CB-UPCSim can be another option to obtain better performance.…”
Section: Discussionmentioning
confidence: 99%
“…• ItemPop, as a non-personalized method, ranks items according to their popularity measured by their interaction numbers. • KIU proposed by [35] is based on the similarity trained by Word2vec to recommend items to users. To obtain user and item representation vectors, it constructs sentences that start with a user identity followed by the identity sequence of the items chronologically consumed by the user.…”
Section: Baselinesmentioning
confidence: 99%
“…Recommendation services aim to model user preferences based on user history interactions, such as item ratings ( Nguyen et al, 2020a ; Hong & Jung, 2018 ; Nguyen, Jung & Hwang, 2020b ; Vuong Nguyen et al, 2021 ). Some of the traditional methods in recommendation systems (RSs) such as matrix factorization (MF) ( Koren, RM & Volinsky, 2009 ; Salakhutdinov & Mnih, 2007 ) or neural collaborative factoring (CF) ( Cheng et al, 2016 ; Dziugaite & Roy, 2015 ; He et al, 2017 ; Nguyen, Nguyen & Jung, 2020c ) are applied to several specific datasets collected from several sources.…”
Section: Introductionmentioning
confidence: 99%
“…The recommended results of these methods achieve acceptable accuracy. The most important goal in an RS is to increase the accuracy of items recommended to users ( Vuong Nguyen et al, 2021 ). This means the RS must be designed to collect as much information as possible from users.…”
Section: Introductionmentioning
confidence: 99%